The Influence of Trust and Promotion on Intention to use Insurance Products at BRI Insurance - Bomantari Gilang Pratiwi; Nyoman Dwika Ayu Amrita; I Made Kartika (Jurnal Dialektika: Jurnal Ilmu Sosial, 2026)
Public interest in using insurance products is still relatively low due to several influencing factors, particularly trust and promotion. BRI Insurance, as one of the insurance companies in Indonesia, needs to understand these factors in order to increase public interest in using insurance products. This study aims to analyze the influence of trust and promotion on the interest in using insurance products at BRI Insurance. The research method used is a literature review of relevant scientific journals published in the last five years. The results of the study indicate that trust and promotion have a positive influence on public interest in using insurance products. Trust increases consumer confidence in the company, while promotion helps enhance public knowledge and awareness of insurance products.